Pelatihan Penulisan Karya Ilmiah bagi Guru-Guru Sekolah Dasar SDN Tuban Kecamatan Pujut Kabupaten Lombok Tengah - syamsurrijal, syamsurrijal; Lalu Jazuli Azhar Mardedi; Muhammad Fathoni; Ni Putu Sinta Dewi (Insan Kreasi Media, 2022)
Abstract: This community service activity (P2M) aims to (1) increase the motivation of SDN Tuban Segala Anyar Village teachers, Pujut District, Central Lombok Regency in writing scientific papers and (2) improve the ability of elementary school teachers Tuban Segala Anyar village in Pujut district, Central Lombok Regency in writing scientific papers. in the form of a research report. The achievement of these goals is carried out through training with discussion methods, questions and answers, demonstrations, and exercises (tutorials). After the training activities, monitoring or evaluation is carried out by the implementation committee to see and assist teachers in writing scientific papers. The result of the study shows that the P2M program went well and smoothly. This program is able to motivate teachers in writing scientific papers and is able to improve teachers' abilities in conducting research and writing research reports. Obstacles that arise at the stage of research and writing research results can be overcome by the method of mentoring. As for suggestions that can be submitted from the results of the P2M program, teachers are expected to have motivation and always cultivate scientific writing activities. Education practitioners are expected to always be able to help teachers in scientific writing activities. For LPPM, the University of Bumigora should always bridge similar programs so that they can continue to be implemented and developed